Study on an advanced borehole heat exchanger for ground source heat pump operating in volcanic island: Case study of Jeju island, South Korea - Kim, Jong Woo; Kim, Yeong-Min; Ko, Yoon Jung; Chen, Qian; Xin, Cui; Oh, Seung Jin (Frontiers in Built Environment, 2022)
This paper presents an advanced borehole heat exchanger that has been developed in order to apply a ground source heat pump to a volcanic island where the existing borehole heat exchangers are inapplicable by local ordinance. The advanced borehole heat exchanger was fabricated and installed at a verification-test site to evaluate its heat capacity in terms of refrigeration ton (RT). The proposed heat exchanger was also compared with the conventional heat exchanger that was made of high-density polyethylene (HDPE) heat exchanger. The thermal response test was carried out by flowing water at various temperatures into the heat exchangers at the fixed flow rate of 180 L/min. The results revealed that the maximum heat capacity for the developed heat exchanger was measured at 63.9 kW, which is 160% higher than that of the high-density polyethylene heat exchanger (39.9 kW). It was also found that the developed HX has the highest heat gain achieving 94 kW as compare to 21 kW for high-density polyethylene-Hx.